Mountain & Alpine Medicine - Burtscher M; 2; Niederseer D (Dynamic Media Sales Verlag, 2020)
Sudden cardiac death (SCD) is an unanticipated and dramatic event resulting from cardiac causes. First reports on SCDs during mountain sports activities date back to the 1970s and 1980s of the last century. Relatively large datasets have been collected in Austria from 1985 onwards initiating systematic recordings and analyses of risk factors and triggers of SCDs during mountain sports activities. The results presented in this publication are derived from a literature search on reported SCDs that occurred during selected mountaineering activities with particular regard to study findings based on data collected in Austria.We found a relatively low SCD risk during mountaineering activities, amounting to about 1 SCD per 1 million activity days when hiking, trekking or ski touring, which is even lower during downhill skiing but higher in competitive cross-country skiing. The risk is much higher in men than in women and increases sharply above the age of 34. Main risk factors include prior myocardial infarction, coronary artery disease, arterial hypertension, hypercholesterolaemia and diabetes mellitus type 2, but regular and sport-specific activities turned out to be important protective factors. Unaccustomed physical exertion, in particular on the first days in the mountains (altitude), prolonged activities without rest and insufficient energy and fluid intake represent important SCD triggers. Besides considering these potential triggers during mountaineering activities, sports medical examination, appropriate pharmacological therapy of risk factors and physical preparation represent preventive key elements.Key Words: Exercise, Mountains, Cardiovascular, Risk, Triggers, Prevention